Serum chloride as a respiratory failure marker in amyotrophic lateral sclerosis - Manera, Umberto; Grassano, Maurizio; Matteoni, Enrico; Bombaci, Alessandro; Vasta, Rosario; Palumbo, Francesca; Torrieri, Maria Claudia; Cugnasco, Paolo; Moglia, Cristina; Canosa, Antonio; Chiò, Adriano; Calvo, Andrea (Frontiers in Aging Neuroscience, 2023)
Respiratory failure is the most common cause of death in patients with amyotrophic lateral sclerosis (ALS) and occurs with great variability among patients according to different phenotypic features. Early predictors of respiratory failure in ALS are important to start non-invasive ventilation (NIV). Venous serum chloride values correlate with carbonate (HCO3-) blood levels and reflect metabolic compensation of respiratory acidosis. Despite its wide availability and low cost, few data on serum chloride as a prognostic marker exist in ALS literature. In the present study, we evaluated serum chloride values at diagnosis as prognostic biomarkers for overall survival and NIV adaptation in a retrospective center-based cohort of ALS patients. We collected all ALS patients with serum chloride assessment at diagnosis, identified through the Piemonte and Valle d’Aosta Register for ALS, evaluating the correlations among serum chloride, clinical features, and other serum biomarkers. Thereafter, time-to-event analysis was modeled to predict overall survival and NIV start. We found a significant correlation between serum chloride and inflammatory status markers, serum sodium, forced vital capacity (FVC), ALS functional rating scale-revised (ALSFRS-R) item 10 and 11, age at diagnosis, and weight loss. Time-to-event analysis confirmed both in univariate analysis and after multiple confounders’ adjustment that serum chloride value at diagnosis significantly influenced survival and time to NIV start. According to our analysis, based on a large ALS cohort, we found that serum chloride analyzed at diagnosis is a low-cost marker of impending respiratory decompensation. In our opinion, it should be added among the serum prognostic biomarkers that are able to stratify patients into different prognostic categories even when performed in the early phases of the disease.